Noragami : stray god. 15 - Adachi, Toka (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2016)
"Tensions are high between Kazuma and Yukiné, but that doesn't stop Yato from wanting to go to his very first Divine Council. This council will include a matchmaking ceremony, where the gods choose soul mates for the mortals of Japan. What could this mean for Hiyori and her future husband?"--